Effect of Cooperative Marketing on Economic Revenue Following Fuel Subsidy Removal in Awka South Local Government Area, Anambra State (UNIZIK Journal of Marketing, 2024)
This study investigates the effect of cooperative marketing on economic revenue following fuel subsidy removal in Awka South Local Government Area (L.G.A) of Anambra State, Nigeria. The specific objectives include assessing the impact of pricing strategies, examining the effectiveness of distribution channels, and evaluating the effect of marketing promotional activities on revenue growth within selected cooperative societies. A descriptive survey research design was employed for this study. The study population comprises all registered cooperative societies in Awka South L.G.A, totaling 686, with membership strength of 7000. A sample size of 134 members was selected using the Taro Yamane formula. Data were collected through structured questionnaires and analyzed using descriptive statistics and chi-square analysis. The findings reveal a statistically significant positive impact of cooperative marketing on economic revenue following fuel subsidy removal in Awka South L.G.A. The chi-square analysis (X²=29.94) indicates a strong association between cooperative marketing practices and economic revenue post-subsidy removal. Based on the findings, recommendations are proposed to enhance cooperative marketing strategies. These include adopting improved pricing strategies to increase net earnings and maintain profit margins, strengthening collaborative relationships with distribution partners to fortify distribution channels and enhance profitability, and investing in promotional activities like trade shows and exhibitions to increase customer awareness and boost revenue generation.
Keywords: Cooperative Society; Cooperative Marketing; Economic Revenue; Fuel Subsidy Removal